Bridging the trust gap: the mediating role of patient satisfaction in physician empathy - Bai, Huanxi; Li, Fei; He, Zhifang (Frontiers in Medicine, 2025)
IntroductionTo explore the mediating effect of patient-perceived physician empathy on patient trust and patient satisfaction.MethodsThe data of 834 outpatients in a top-three hospital in Jiangxi province were collected, and the general data questionnaire, diagnosis and treatment relationship empathy scale, patient trust scale and PDRQ-15 scale were used to investigate the relationship between variables, and the mediation effect was analyzed by process.ResultsThere was a significant positive correlation between doctors' empathy and patients' trust. Patient satisfaction plays a partial mediating role between perceived physician empathy and patient trust. Physician empathy affects patient trust partly through patient satisfaction.DiscussionOn the basis of ensuring the quality of outpatient treatment, hospitals should strive to improve the doctor's visiting ability and service quality, so as to improve the patient's medical experience and satisfaction level, and thus ease the doctor-patient relationship.